ACTR-61. A RANDOMIZED PHASE 2 TRIAL OF CEDIRANIB IN COMBINATION WITH OLAPARIB VERSUS BEVACIZUMAB IN PATIENTS WITH RECURRENT GLIOBLASTOMA. (11th November 2019) - Arrillaga-Romany, Isabel; Sahebjam, Solmaz; Picconi, David; Campian, Jian; Giglio, Pierre; Drappatz, Jan; Aiken, Robert; Villano, John; Lee, Eudocia; Welch, Mary; Ellingson, Benjamin; Ney, Douglas; et al.
Abstract: BACKGROUND: Like most proliferating tumors, GBM relies heavily on accurate DNA repair for maintenance of genome stability. Dysfunction in repair of both single and double strand DNA breaks by PARP inhibition and impairment of homologous recombination, respectively, would be synthetically lethal. In this study we combined the PARP inhibitor olaparib with cediranib, a pan VEGF receptor inhibitor. Cediranib may mediate disruption in the homologous recombination pathway through its antiangiogenic properties. METHODS: Through the Experimental Therapeutics Clinical Trials Network, we performed an open-label randomized phase II study of bevacizumab (BEV)- naive adult patients with first or second recurrence of glioblastoma after radiation and temozolomide. Patients were randomized 1:1 to receive either olaparib 200 mg by mouth twice daily with cediranib 30 mg by mouth daily or BEV 10 mg/kg IV every 2 weeks. The primary endpoint was progression-free survival at 6 months (PFS6). Secondary endpoints included safety and overall survival. Exploratory objectives included blood, tissue and imaging-based biomarkers of response to treatment. RESULTS: Seventy patients were enrolled. Median age was 60.5 years (range: 19–79), 39% females, median KPS was 90 (range: 60–100). Baseline characteristics were well balanced. With a data cut-off of 5/2/2019, PFS6 was 14% [95% CI 4–30%] in the cediranib/olaparib arm vs 30.9% [95% CI 12.7–51.2%] in the BEV arm. Median OS was 247 days in the cediranib/olaparib arm vs 201 days in the BEV arm, HR 0.816, 95% CI (0.431, 1.546). Related grade 3, 4 or 5 toxicity was experienced in 29% vs 12% of patients for the cediranib/olaparib vs BEV arm. CONCLUSION: Treatment with cediranib/olaparib failed to increase PFS and OS in patients with recurrent GBM. Blood, tissue and imaging correlates will be presented to help understand why this treatment combination was unsuccessful.